Encouraging informed self-management: the MUNCH initiative. - Kirkland F; Burton C; Pearson N; Grant J (Journal of Diabetes Nursing, 2007)
The MUNCH (Making Useful Nutritional Choices for Health) initiative is a new scheme that demonstrates the use of local innovation to meet the needs of a local population with diabetes. It incorporates structured education, self-management, behaviour change and goal-setting strategies.